THE CONCEPT OF ROAD NETWORK DEVELOPMENT BASED ON LOCAL RESOURCES AND WISDOM IN PARTNER REGIONS AROUND THE NATION'S CAPITAL CITY - Junaidi Junaidi; Sakti Adji Adisasmita; Muhammad Saleh Pallu; Muhammad Isran Ramli (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2022)
The development of the National Capital City (NCC) will certainly attract many people to come and have activities around the NCC area and not within the NCC area, this is because the development is a limited area with the concept of an integrated smart city, blue city, forest city. Restrictions on movement in NCC areas will certainly cause problems with road network connectivity around NCC partner areas, so it is deemed necessary to formulate a road network development concept that maintains NCC as a limited area but becomes a trigger for economic growth in partner areas. The purpose of this paper is to formulate a new road network development concept based on local wisdom and resources of each partner area around NCC. The method used in this research is a literature study using data sources from literature and reading materials as well as data from reliable sources. The data were analyzed based on transportation theory and road network development theory. The results of this study resulted in the concept of developing a new road network to several areas such as in Senoni (Kutai Kartanegara Regency), Gusig (West Kutai Regency) and Tukuq (Central Kalimantan Province Border).